Early-life adversity shapes the relationship between growth and reproduction in free-ranging female rhesus macaques - Rachel M. Petersen; Sam K. Patterson; Anja Widdig; Cassandra M. Turcotte; Susan C. Antón; Scott A. Williams; Ashly N. Romero; Samuel E. Bauman Surratt; Angelina Ruiz-Lambides; Michael J. Montague; Noah Snyder-Mackler; Lauren J. N. Brent; et al. (Proceedings of the National Academy of Sciences, 2026)
Life history theory predicts that organisms allocate resources across physiological processes to maximize fitness. Under this framework, early-life adversity (ELA) which limits energetic capital could shape investment in growth and reproduction, ultimately contributing to evolutionary fitness. Integrating 64 y of long-term demographic information with cross-sectional behavioral and physiological data from female rhesus macaques ( Macaca mulatta ; n = 163 to 2,105 females depending on the analysis), we tested whether naturally occurring ELA influences investment in the competing physiological demands of growth and reproduction. By analyzing ELA, growth, and reproduction in the same individuals, we also assessed whether adversity intensifies constraints and induces trade-offs between life history domains. Similar to cohort effects described in other species, we found that ELA was associated with modified growth, delayed reproductive maturity, and small adult body size. These effects largely reflected generalized constraints: females that experienced growth limitations also exhibited reproductive concessions, with ELA linked to reduced investment in both. Interestingly, however, two types of adversity were associated with shifts in growth–reproduction trade-offs, such that ELA-exposed females invested relatively more in reproduction at the expense of growth. Finally, we examined how traits modified by ELA related to lifetime reproductive success, addressing understudied links between ELA, life history, and fitness. Across the population, starting reproduction earlier and maintaining a moderate reproductive rate conferred the greatest number of surviving offspring. These findings suggest that ELA impacts key life history traits as well as the relationships between them, and can constrain individuals from adopting the most optimal reproductive strategy.